Haiti : Joint Staff Advisory Note of the Annual Progress Report on Implementation of the Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Falling international prices have helped lower Haiti's inflation, but base money growth has continued to be higher than targeted in the program. The paper discusses Haiti's Annual Progress Report on Implementation of the Poverty Reduction Strategy Paper. In the area of economic governance, recent advances have been made to increase transparency and efficiency in the use of public resources and external assistance. These include changes in the legal framework for budget formulation and execution, the setting up of critical institutions and agencies, and efforts to disseminate basic information.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet